Pengembangan Panduan Praktikum Basic Life Skills bagi Mahasiswa PGSD STKIP PGRI Banjarmasin - M Saufi; Sa'adah Erliani; Hj. Maryam Agustina (Program Studi PGSD STKIP PGRI Banjarmasin, 2021)
Basic Life Skills (Basic Life Skills) are the ability and knowledge of a person to dare to face the problems of life and life proactively seek and find solutions so that they are finally able to overcome them with the ability to interact and adapt with others, decision-making skills, problem solving, critical thinking, thinking. creative, effective communication, fostering interpersonal relationships, self-awareness, empathy, coping with emotions, and coping with stress. Basic Life Skills This has been implemented by the Education System in Japan for a long time, but in Indonesia, activities like this tend to be rarely carried out, even though this program is very important. Basic Life Skills for Elementary School is one of the flagship programs initiated by the PGSD STKIP PGRI Banjarmasin Study Program. This activity is an open activity that involves children to participate in all activities, social life, and encourages the growth and development and welfare of children. Basic Life Skills for Elementary School at PGSD STKIP Banjarmasin will take effect in the 2021/2022 academic year. However, the problem is that there are no available teaching materials or references, both offline and online. Therefore, as an initial stage, researchers want to develop one form of teaching material, namely the Basic Life Skills Practical Guide. This study aims to determine the feasibility of basic life skills practicum guides from aspects of validity and practicality, so this research is included in the type of development research. The development models referred to are the 4D and Nieveen models. Based on the results of expert validation and student assessment through validation sheets and practicality sheets, data obtained that the average score for the validity of the guide is 60.33 with a score range of 14≤x≤70 so it is included in the very valid criteria. Meanwhile, the average practicality score of the guide is 39.6 with a score range of 10≤x≤50 so that it is included in the practical category. These results indicate that the Basic Life Skills Practicum Guide for PGSD STKIP PGRI Banjarmasin students is feasible to use.